Pengaruh Rasio Profitabilitas, Arus Kas, Nilai Tukar, Suku Bunga dan Inflasi Pada Financial Distress Pada Perusahan Manufaktur - Agustinus Nicolas Saputra; Ratih Kusumastuti (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This study aims to determine the effect of profitability ratios, cash flows, exchange rates, interest rates, and inflation on financialdistress in manufacturing companies. The research method used in this study includes a statistical description test, classicassumption test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results of this study can be concluded:1) Profit, cash flow, leverage, inflation and exchange rates simultaneously affect financial distress in manufacturing sectorcompanies; 2) profitability affects financial distress in manufacturing companies; 3) Cash flow affects financial distress inmanufacturing sector companies; 4) The exchange rate has an effect on financial distress in manufacturing sector companies; 5)Interest rates have no effect on financial distress in manufacturing sector companies; and 6) Inflation has no effect on financialdistress in manufacturing sector companies.